2018
DOI: 10.1097/md.0000000000010127
|View full text |Cite
|
Sign up to set email alerts
|

Which are the best Chinese herbal injections combined with XELOX regimen for gastric cancer?

Abstract: Background:The optimal Chinese herbal injections (CHIs) combined with XELOX regimen for patients with gastric cancer remains elusive. The aim of our network meta-analysis (NMA) is to explore the best options among different CHIs for gastric cancer.Methods:PubMed, Embase, the Cochrane Library, the China National Knowledge Infrastructure Database (CNKI), Wan-fang Database, Cqvip Database (VIP), China Biology Medicine disc (CBMdisc) were searched to identify RCTs which focused on CHIs against gastric cancer. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Previous studies have confirmed the effectiveness of CKI in the treatment of GC [20,21] but did not explore the molecular biology. To better analyze and predict the molecular mechanism of CKI in the treatment of GC, this study adopted the network pharmacology and molecular docking method.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed the effectiveness of CKI in the treatment of GC [20,21] but did not explore the molecular biology. To better analyze and predict the molecular mechanism of CKI in the treatment of GC, this study adopted the network pharmacology and molecular docking method.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it has passed the standardized Good Manufacturing Process (GMP) certi cation and is often used clinically to treat gastric cancer [9]. After multiple systematic reviews and meta-analysis studies, it was found that CKI can not only improve the clinical e cacy of gastric cancer patients but also alleviate the adverse effects of radiotherapy and chemotherapy [48][49][50]. Cancer is a complex disease arising from changes in multiple biological networks [51].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbal injection (CHI) is a new formulation with rapid action and high bioavailability and made from components extracted from traditional Chinese herb using modern technology . It is widely used in the treatment of cardiovascular diseases, cancers and respiratory diseases . Although numerous traditional pairwise meta‐analytic reviews have reported on the efficacy of many CHIs that could be used to treat mycoplasma pneumonia in children, the effect of which kind of injection is the best remains unclear.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…18 It is widely used in the treatment of cardiovascular diseases, cancers and respiratory diseases. [19][20][21][22][23][24] Although numerous traditional pairwise metaanalytic reviews have reported on the efficacy of many CHIs that could be used to treat mycoplasma pneumonia in children, [25][26][27][28] the effect of which kind of injection is the best remains unclear. This is because the traditional pairwise meta-analysis can only achieve direct comparison between the two interventions and cannot comprehensively evaluate the efficacy of various interventions.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%